2012
DOI: 10.1111/j.1365-2311.2012.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Fuelling flight in a parasitic wasp: which energetic substrate to use?

Abstract: 1. Flight is an energy-demanding behaviour in insects. In parasitic wasps, strategies of nutrient acquisition and allocation, resulting life-history trade-offs and relationships with foraging strategies and resource availability have received much attention. However, despite the ecological importance of dispersal between host and food patches, and the great impact energy diverted to flight should have on lifetime reproductive success, the eco-physiology of flight in parasitoids is poorly understood.2. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 75 publications
4
29
0
Order By: Relevance
“…The proportion of diploid males further corresponds to that expected when sex ratios are equal (Fauvergue et al, 2015). Field and laboratory studies further revealed that adult females are good dispersers, with a flight velocity estimated at 0.2 m.s -1 (Schneider et al, 2002;Desouhant et al 2003;Amat et al, 2012).…”
Section: Biological Modelsupporting
confidence: 52%
“…The proportion of diploid males further corresponds to that expected when sex ratios are equal (Fauvergue et al, 2015). Field and laboratory studies further revealed that adult females are good dispersers, with a flight velocity estimated at 0.2 m.s -1 (Schneider et al, 2002;Desouhant et al 2003;Amat et al, 2012).…”
Section: Biological Modelsupporting
confidence: 52%
“…Maleā€biased dispersal patterns have been reported in nonsocial insects by Downey et al () and might be explained in V. canescens by local resource competition. Males and females of V. canescens are known to be good fliers (Amat et al, ; Desouhant, Driessen, Amat, & Bernstein, ; Metzger, Fischbein, et al, ), meaning that dispersal should contribute strongly to decreasing the probability of sib encounters. Hence, if maleā€biased dispersal affected the population structure in Nice and consequent encounter rates between relatives, it should be a weak effect compared to the effect of dispersal of the two sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Immature development and adult life each last ~3 weeks (at 25Ā°C), and females lay eggs during most of their adult lifespan (Metzger, Bernstein, & Desouhant, 2008), leading to overlapping generations. Field and laboratory studies have further revealed that adult females are good dispersers with a flight velocity estimated at 0.2 m/s (Amat et al, 2012;Desouhant, Driessen, Lapchin, Wielaard, & Bernstein, 2003;Schneider et al, 2002).…”
Section: The Biological Model and Its Mating Systemmentioning
confidence: 99%
“…One important factor that was not measured in this study is the quantity of nutrient reserves that fuel somatic maintenance, locomotion, and future egg manufacture (Jervis et al., ). Nutrient reserves, such as glycogen and fat substantially affect parasitoid performance (Amat et al., ), and recent research indicates that age of the mother affects nutrient provisioning and subsequent nutrient dynamics (up to adulthood) in the offspring (Muller et al., ), but it has remained unclear how females allocate these resources to various functions. Further studies could elucidate the adaptive response of female parasitoids to environmental factors by analyzing patterns of resource allocation, as well as fitnessā€related traits.…”
Section: Discussionmentioning
confidence: 99%